MODERN APPROACHES TO TEACHING AND ASSESSING ENGLISH LANGUAGE SKILLS BASED ON CEFR STANDARDS - Abduraximov Murodbek Baxtiyor oʻgʻli; Xo'shboqov Sarvar Bahrom o'gli; Husanov Abdurahmon Juma oʻgʻli (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract The Common European Framework of Reference for Languages (CEFR) has become one of the most influential instruments guiding English language pedagogy and  assessment  across  educational  systems  worldwide.  This  article  investigates contemporary  instructional  and  evaluative  approaches  that  align  with  CEFR descriptors, focusing on how action-oriented tasks, communicative methodology, and authentic assessment enhance learner performance across the four core language skills. Drawing on document analysis, comparative research on international examinations, and expert-based synthesis, the study demonstrates that CEFR-informed teaching not only ensures transparency in learning outcomes but also supports more reliable and equitable  assessment  procedures.  The  findings  reaffirm  that  integrating  CEFR standards  with  task-based  learning,  formative  assessment,  and  technology-assisted feedback significantly improves language proficiency development, learner autonomy, and instructional coherence.